Antecedents of export performance among Chinese smartphone manufacturers in ASEAN: The moderating effect of competitive intensity - Di, Zhang Meng (2023)
This study explores the antecedents that influence the export performance of Chinese smartphone manufacturers in ASEAN, while considering the moderating effect of competitive intensity. Data was collected from Chinese smartphone manufacturers using questionnaires that focused on their involvement in specific export activities. A non-probability sampling procedure was used to select the participating firms. Based on the theoretical framework, this study employed Partial Least Squares Structural Equation Modeling (PLS-SEM) for data analysis. The findings reveal significant relationships between market-seeking and export performance, as well as between relational assets-seeking and export performance. Notably, technical capability exhibited a significant impact on export performance. However, the study found that the impact of innovation capability on export performance is not significant. The study also revealed that competitive intensity moderates the relationship between innovation capability and export performance, along with the relationship between technical capability and export performance. Conversely, competitive intensity did not impact the relationship between market-seeking and export performance, nor the relationship between relational assets-seeking and export performance. Hence, this study presents a holistic assessment of Chinese smartphone manufacturers' export performance by accounting for the overlooked antecedents through moderating competitive intensity. This study has far-reaching consequences for export academics and practitioners, particularly in terms of understanding the fundamental concept of internationalizing small-and medium-sized manufacturing enterprises.